O termo de ajustamento de conduta como política de prevenção dos delitos patrimoniais em unidades de transporte público da cidade de Manaus/Am - Barros, Carlos Augusto Alvarenga De (2021)
This research, whose closure is a product in the form of a Technical Note, is part of the research agenda dedicated to understanding the processes of governance and social participation in public policies that are being formulated and implemented to improve public safety in public transport. from the city of Manaus in the state of Amazonas, due to the worrying amount of property crimes that took place inside the buses. With the objective of combating this adverse reality and offsetting the multiple losses and grievances, a Conduct Adjustment Term (TAC) was established between the Public Prosecutor's Office and representatives related to crime prevention and the transport companies' union. The research elaborated through the case study, and the final product presented in the form of a Technical Note, focuses on TAC as a public policy instrument that is inserted in the debate on contemporary governance. The analysis is centered on the role of public bodies responsible for monitoring and overseeing the various policies instituted, as well as on the role of the Transport Union. As for the results, aspects that highlight the features of the institutional design of the TAC and its governance modus, as well as its efficiency in fighting crime, which has been practiced since the signing of the aforementioned agreement, as well as the challenges arising from it, stand out. of the existing asymmetries in the relations between the transport companies and the public authorities, on the one hand, and those affected on the other. At the end, with the presentation of a product, in the form of a Technical Note, the aim is to contribute to alleviate a problem that afflicts the most vulnerable population in the city of Manaus.